Surgical pathology of thyroid gland in pediatric patients - Oré, Juan (2019)
Introduction. The surgical pathology that involves the thyroid gland in pediatric patients has less presentation that adults, but if presented, the possibility of malignancies should be taken into consideration despite the age of the patient. Objective. To describe the previous and posterior surgical characteristics of the pedaitric patients who underwent thyroid gland surgery. Methods. Clinical histories of the patients surgically treated with cystic, neoplastic or inflammatory pathology of the thyroid gland between january 2008 and january 2017 were reviewed. Results. Sixty cases were intervened, being the female sex the predominant with 80% of the cases and 56,6% between 13 to 16 years. The benign neoplasms correspond to 51,7% of the total. The hemithyroidectomy was the most realized surgery with 60% of the cases and in second place the resection of the remaining gland to complete the total thyroidectomy. We had two cases with transient hypocalcemia, and in one case permanent hypocalcemia with vocal cord paralysis, that required a tracheotomy. Conclusion. The treatment of neoplasms or thyroid cysts is eminently surgical, with minimal morbidity and lower mortality. Tumors of the thyroid gland are not exceptional presentation in pediatric patients.